Penerapan Metode Penelitian Kuantitatif Dalam Manajemen Pendidikan Islam: Analisis, Tantangan, Dan Prospek - Afifah Barkatul Atqiya; Asep Irfan Fanani; Irawan Irawan (Peneliti.net, 2023)
This study aims to investigate the application of quantitative research methods in the context of Islamic education management. In order to achieve this goal, the study identifies the most relevant and effective quantitative research methods in understanding various aspects of Islamic education management. It also identifies the challenges faced in the application of quantitative research methods in the context of Islamic education and provides prospects for future development in this field. The results show that there are several quantitative research methods that are relevant in the context of Islamic education management. Some commonly used methods include surveys, experiments, secondary data analysis and regression analysis. In addition, the study also identified some challenges faced in applying quantitative research methods in Islamic education, such as difficulties in measuring qualitative variables, constraints